First Reconstruction of Kinship in a Scalloped Hammerhead Shark Aggregation Reveals the Mating Patterns and Breeding Sex Ratio - Marie, Amandine D.; Herbinger, Christophe; Fullsack, Philippe; Rico, Ciro (Frontiers in Marine Science, 2019)
Sharks constitute one of the most threatened clades (Selachimorpha) of all marine fish, and substantial management efforts are required to help the recovery of their populations worldwide. Despite its significant impact on population dynamics and conservation, sharks’ reproductive and philopatric behavior has received little attention in fisheries management. The scalloped hammerhead shark (Sphyrna lewini), an endangered species listed on the IUCN’s Red List and on the CITES’ Appendix II, is an apex predator that potentially exhibits female philopatry to mating grounds. We reconstructed, for the first time in an open ocean species, the relationship among 166 juvenile individuals caught in a recently discovered aggregation of the Rewa Delta, Fiji, and determined the sample population’s mating system using 6,437 SNPs. Using two software packages, COLONY2 and SNP PEDIGREE, results revealed very high consistency in the identification of full and half sib. Moreover, COLONY2 allowed us to identify an equal breeding sex ratio for each cohort analyzed for this population (1.04:1; 1.02:1), as well as several cases of multiple paternity and numerous matings of the same male with different females suggesting polygynandry for this species. These findings reveal additional information about the complex life history of the scalloped hammerhead shark.